1985
DOI: 10.1111/j.1600-0536.1985.tb01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Epicutaneous induction of tolerance with acrylates and related compounds

Abstract: Epicutaneous application of acrylates and related compounds 14 and 7 days before sensitization with either methyl acrylate or trimethylol propane triacrylate induced tolerance to the resultant contact reactions. This tolerance could not be correlated with either the degree of cross reactivity between these compounds or with their ability to react covalently with amino or sulphydryl groups of proteins. These results are discussed in relation to other epicutaneous tolerizers in the dinitrobenzene and poison ivy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Dimethacrylates, according to Björkner (10) and Parker (11), have little sensitizing capacitiy when tested in guinea pigs, while Cavelier (12) has reported that EGDMA, DEGDMA, TREGDMA and TGGDMA are moderate allergens in the guinea‐pig maximization test. Several cases of contact allergy to EGDMA are described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Dimethacrylates, according to Björkner (10) and Parker (11), have little sensitizing capacitiy when tested in guinea pigs, while Cavelier (12) has reported that EGDMA, DEGDMA, TREGDMA and TGGDMA are moderate allergens in the guinea‐pig maximization test. Several cases of contact allergy to EGDMA are described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This ring will bear epitopes not present in either TMPTA or MeAc and it may exert an influ ence on the vinyl bond, which would render the bond nonantigenic in terms of antibodies raised against TMPTA/BGG or MeAc. Previously, we reported [8] that it is possible to elicit positive skin test responses to 4VP in guinea pigs sensitized to either TMPTA or MeAc, but that 4VP-sensitized animals only re sponded to a 4VP skin test. Therefore, it appears that cell-mediated immune responses in guinea pigs may involve recognition of different epitopes than does the humoral response.…”
Section: Discussionmentioning
confidence: 99%
“…1) have been in vestigated in terms of their immunogenicity as as sessed by the in vivo induction of antibody. The abil ity of the acrylates to induce antibodies and the spe cificities of these antibodies were compared with data published previously on the in vivo sensitization ca pacity and cross-reactivity between the acrylates [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Methyl acrylate caused sensitization in guinea pigs in various experimental systems [14,15]. In animal studies, methyl acrylate can also induce tolerance to sensitization with structurally related substances [15].…”
Section: Skin Sensitizationmentioning
confidence: 99%
“…In animal studies, methyl acrylate can also induce tolerance to sensitization with structurally related substances [15].…”
Section: Skin Sensitizationmentioning
confidence: 99%